Parkraumbewirtschaftung in innenstadtnahen Mischgebieten. - Grötsch, Melanie; Höhnberg, Gunther; Kirchhoff, Peter (Deutscher Verkehrs-Verl., 2004)
Die Ausführungen betreffen Untersuchungen, die im Rahmen des in München bearbeiteten Forschungsprojekts MOBINET durchgeführt wurden. Die Darstellung der Untersuchungsergebnisse beschränkt sich hier auf den Münchener Stadtbezirk Alt-Schwabing. Gleichartige Untersuchungen, die zu ähnlichen Ergebnissen führten, erfolgten in den Münchener Stadtbezirken Schwabing-West und Lehel. Inzwischen wird von der Stadt München eine Ausweitung der Parkraumbewirtschaftung auf weitere Stadtbezirke vorbereitet. difu

It has become necessary to introduce system of commercial control over parking space in mixed business / residential areas near city centres whenever the demand exceeds the parking lots available and additional space cannot be provided short term by way of building more garages. To deal with this shortage, a system of priorities has to be devised to meet the requirements of residents, commercial firms, visitors and employees. This will effectively force out employees parking for longer periods although it can be expected that, in areas well served by public transport, they may feel prompted to give up using their private cars and switch to 'Park + Ride' as the case may be. This report is based on the example provided by the Alt-Schwabing district of Munich, and highlights the methodology applied to this research project and its results. difu
Keywords: Stadtverkehr; Individualverkehr; Autoverkehr; Parken; Innenstadt; Stadtteil; Mischgebiet; Parkraumbewirtschaftung; Parkregelung; Maßnahme